Effectiveness Test Of Green Betel Leaf Ethanol Extract Gel Preparation (Piper Betle L.) Against Pseudomonas Aeruginosa Bacteria - Dumartina Hutauruk; Jon Kenedy Marpaung; Nuranti Nurmela; Jansen Asriel Ginting (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Pseudomonas aeruginosa is an opportunistic pathogenic bacterium commonly associated with nosocomial infections, particularly in immunocompromised patients. Inappropriate use of antibiotics can lead to resistance, highlighting the need for safer and more effective alternative treatments. Green betel leaf (Piper betle L.) contains active compounds such as flavonoids, tannins, and saponins that exhibit antibacterial properties. This study aims to evaluate the effectiveness of an ethanol extract gel formulation of green betel leaves against the growth of Pseudomonas aeruginosa. The methods included ethanol extraction of betel leaves through maceration, formulation of gels with varying extract concentrations, and antibacterial activity testing using the disk diffusion method. The results showed that the ethanol extract gel was able to inhibit the growth of P. aeruginosa, with inhibition zones increasing along with higher extract concentrations. In conclusion, the ethanol extract gel of green betel leaves has potential as a natural antibacterial agent against Pseudomonas aeruginosa.